An intensified trans-sectoral nutritional intervention in malnourished patients with chronic pancreatitis improves diseases prognosis and identifies potential biomarkers of nutritional status - Wiese, Mats L.; Frost, Fabian; Meyer, Fatuma; Müller, Josefine; Valentini, Luzia; Rischmüller, Karen; Lamprecht, Georg; Steveling, Antje; Lerch, Markus M.; Aghdassi, Ali A. (Frontiers in Medicine, 2024)
Background: Malnutrition is a common complication in chronic pancreatitis and associated with reduced quality of life and life expectancy. Nutritional support is considered mandatory in malnourished patients with chronic pancreatitis but there is only scarce evidence on optimal treatment modalities and the efficacy of nutrition therapy. Here, we investigated the feasibility and efficacy of an intensified nutritional intervention in malnourished patients with chronic pancreatitis and aimed to identify suitable indicators for monitoring nutritional status.We performed a single-arm feasibility study, in which malnourished patients with chronic pancreatitis received an intensified trans-sectoral nutritional intervention for 6 months. Multimodal treatment comprised face-to-face dietary counselling, oral nutritional supplementation, and a complementary telephone-based nutrition and exercise coaching. Patients underwent follow-up examinations after 28, 90, and 180 days, when we assessed changes in anthropometric and body composition measures, muscle function, Chronic Pancreatitis Prognosis Score (COPPS), as well as blood parameters and intestinal microbiota composition.Results: Eleven out of 73 patients initially screened for study participation were enrolled in the trial of which 9 subjects (age (mean±SD): 56.2 (±14.8) years; male: 67%; alcoholic etiology: 44%) underwent the complete intervention. Patients gained a median of 5.3 kg (8.6%) body weight, including 1.6 kg skeletal muscle mass, and significantly increased gait speed (p < 0.001). Ameliorated nutritional status and muscle function were associated with increased blood levels of IGF-1 and cholinesterase as well as altered gut microbiota composition on the phyla and genera level. Moreover, significant improvements in COPPS indicated reduced disease severity after 90 and 180 days.Malnourished patients with chronic pancreatitis benefit from intensified nutritional therapy. Besides ameliorated nutritional status, a multimodal intervention can improve muscle function as well disease prognosis. Future studies are needed to prove superiority to standard-of-care and to validate potential biomarkers for prospective monitoring of nutritional status.